Infection control practice in countries with limited resources - Alp Emine; Leblebicioglu Hakan; Doganay Mehmet; Voss Andreas (BMC, 2011)
Abstract Nosocomial infections and their control are a world-wide challenge. The prevalence of nosocomial infections is generally higher in developing countries with limited resources than industrialized countries. In this paper we aimed to further explain the differences with regard to infection control challenges between Turkey, a country with "limited" resources, and the Netherlands, a country with "reasonable" resources. Infrastructure of hospitals, low compliance of hand hygiene, understaffing, overcrowding, heavy workload, misuse of personal protective equipments, late establishment of infection control programme are major problems in limited-resources countries. These problems cause high infection rates and spread of multi-drug resistant pathogens. To improve the control and prevention of infections in countries with limited resources, a multi-facet approach is needed.